Dryland crop model based approaches to guide the climate adaptation of crop and livestock systems across scales in Senegal. - Vincent Vadez; Amir Hajjarpoor; Malick Ndiaye; Jerome Bossuet (2023)
Sorghum sowing density trial conducted by IRD/IGE/CERAAS with Benin Institute student, combining crop varietal diversity and land management interventions at plot level to improve integrated predictive crop modelling. The vision is to develop crop fitness mapping evidence (interaction with development partner MyAgro for scaling). Initiate a socio-economic study on cross-sectoral fodder resource issue in Senegal with ISRA BAME. Evidence to be presented at crop diversification science policy dialogues 14 Dec 2023 ICRISAT led event-